Sixth Order Polynomial Model And Skyhook Algorithm Based Fuzzy Logic Control Of Magnetorheological Damper For Automotive Suspension System - Ubaidillah, . (2010)
This study deals with the investigation on the modeling of a Magne-Ride damper and its uses in overcoming the effects of road disturbance to the vehicle ride comfort. It was begun from the study on the performance of a sixth order polynomial approach to model the nonlinear hysteresis behavior of magnetorheological (MR.) damper. The polynomial model was developed based on curve fitting from the experimental results which consists of a pair subsystem namely positive and negative acceleration corresponding to the upper and lower curves. The performance of the proposed polynomial model was compared with a well known non-parametric technique namely inverse model. The energy dissipated and equivalent damping coefficient of the MR damper in terms of input current and displacement amplitude were also investigated. From the simulation results, the sixth order polynomial model shows better performance in describing the non-linear hysteresis behavior of MR damper compared to the inverse model. The force tracking control in both simulation and experimental studies demonstrate that a close-loop PI control has the ability to track the desired damping force well. The governing equations of motions were formulated and integrated with skyhook control. Skyhook policy was then adapted in the development of a fuzzy logic control to enhance the ride performance. The performance of fuzzy logic control was compared with the on-off and continuous skyhook control in time domain. The results show that skyhook algorithm based fuzzy logic control gives better performances than its counterparts.